2009
DOI: 10.1007/s12257-008-0242-x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase from Bacillus sp. VUS and its role in the decolorization of textile dyes

Abstract: ^Äëíê~Åí= Peroxidase was purified by an ion exchange chromatography followed by gel filtration chromatography from dye degrading _~Åáääìë sp. strain VUS. The optimum pH and temperature of the enzyme activity was 3.0 and 65°C, respectively. This enzyme showed more activity with å-propanol than other substrates tested îáò. xylidine, 3-(3,4-dihydroxy phenyl) Lalanine (L-DOPA), hydroxyquinone, ethanol, indole, and veratrole. Km value of the enzyme was 0.076 mM towards å-propanol under standard assay conditions. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…SUK1 and Bacillus sp. VUS had optimum pH of 3.0 [26] [27]. Our present studies show that actinobacterial POXs have optimum pH of 7.0.…”
Section: Effect Of Ph On Total Pox Activity and Stabilitysupporting
confidence: 52%
“…SUK1 and Bacillus sp. VUS had optimum pH of 3.0 [26] [27]. Our present studies show that actinobacterial POXs have optimum pH of 7.0.…”
Section: Effect Of Ph On Total Pox Activity and Stabilitysupporting
confidence: 52%
“…Lignin peroxidase catalyzes the oxidative breakdown of azo dye Disperse orange 3, resulting in the formation of nitrobenzene as a major product (Zhao et al 2006). The role of purified lignin peroxidase in the degradation of azo dyes like Methyl orange and Methyl red has also been reported (Gomare et al 2008;Dawkar et al 2009;Ghodake et al 2009). …”
Section: Introductionmentioning
confidence: 88%
“…Earlier reports on bacterial peroxidases purified from Bacillus sp. VUS (Dawkar et al 2009) and Acinetobacter calcoaceticus NCIM 2890 (Ghodake et al 2009) showed molecular weights of 43 kDa and 110 kDa, respectively. Figure 4 shows the effects of pH and temperature on peroxidase activity.…”
Section: Characterization Of Purified Peroxidasementioning
confidence: 99%
“…Peroxidase oxidized n-propanol much faster as compared to other substrates (hydroxyquinone, L-DOPA and veratrole) which are phenolic and aromatic compounds. The K m and V max values for peroxidase with n-propanol as a substrate were found to be 0.076 mM and 3 9 10 2 lM, respectively (Dawkar et al 2009). The presence of H 2 O 2 showed an increase in the peroxidase activity by 1.33-fold, with Km 0.046 mM for H 2 O 2 (Fig.…”
Section: Enzyme Activities While Decolorization In Batch Culturementioning
confidence: 99%